CONCEPTUAL PRINCIPLES OF ENSURING THE COMPANY'S INTERNATIONAL COMPETITIVENESS - KHACHATRYAN, VALENTYNA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article conducts a comparative analysis of scientists' opinions on the interpretation of the concept of "international competitiveness of the enterprise", which showed that each scientist interprets the concept from different positions, the most common of which is compliance with international market requirements, taking into account the main factors that shape competitive advantage. Based on the analysis, a number of essential characteristics of the concept of international competitiveness identified and the author's definition of the studied concept formulated. The process of ensuring international competitiveness in the context of the interpretation of modern scientists characterized and the main tasks of the enterprise to ensure international competitiveness from the point of view of different scientists highlighted. The role of competitive advantages in international competition substantiated and their main principles characterized. It is determined that the competitive advantage is formed on the basis of innovations, improvements and changes is formed on each component of the value system involved in the process of creating a product or service, its use and covers stakeholders: suppliers, intermediaries, buyers, supported by continuous improvement. Require the improvement of its sources, which can result from any activity in the value chain, from product development to service. It argued that maintaining an advantage requires a global approach to strategy, as an enterprise cannot sustain a competitive advantage in international competition for long if it does not use and expand its country-based advantages through a global approach to strategy. Based on the conducted analysis the mechanism of maintenance of the international competitiveness of the enterprise is constructed.
Keywords: competitiveness; international competitiveness of the enterprise; competitive advantage; competition; model of five forces of M. Porter